2017
DOI: 10.26905/jkdp.v21i2.393
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of CSR and Profitability on the Influences of GCG Mechanisms to the Firm Value

Abstract: The purpose of this research was to determine the causal relationship among GCG mechanism, financial performance, CSR and firm's value. The model of the research was constructed by using financial performance and CSR as intervening variables on the effect of GCG mechanism to firm's value. This research was accomplished on companies listed in Jakarta Islamic Index (JII) in Indonesia Stock Exchange for the period of 2007-2013. The result showed that GCG mechanism tended to reject every CSR financing. CSR was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…This positive value indicates that the influence that occurs between the corporate financial performance and firm value is a positive influence. This is similar to what was conveyed by Mai (2017) who supported that there was a positive influence between corporate financial performance and firm value with ROE and EPS as the indicators. ROE is a ratio that could measure the firm effectiveness in managing its finances by using funds invested by investors.…”
Section: Partial Least Square Resultssupporting
confidence: 88%
“…This positive value indicates that the influence that occurs between the corporate financial performance and firm value is a positive influence. This is similar to what was conveyed by Mai (2017) who supported that there was a positive influence between corporate financial performance and firm value with ROE and EPS as the indicators. ROE is a ratio that could measure the firm effectiveness in managing its finances by using funds invested by investors.…”
Section: Partial Least Square Resultssupporting
confidence: 88%
“…One of the most important and crucial financial performance ratios is profitability ratios (R. Ernayani, Robiyanto, & Sudjinan, 2017;Mai, 2017). Profitability is an indicator of company performance associated with the ability of companies to gain kembali dengan menggunakan GARCH (Generalized Autoregressive Conditional Heteroscedasticity).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested (i.e. Chavali and Rosario (2018); Mai (2017)) that profitability might be one of the factors believed to strengthen the relationship of company growth with debt policy. Hence, this present research is important, as there is a gap found in the relationship between company growth and debt policy by developing a research model.…”
Section: Background Of the Studymentioning
confidence: 99%